2017
DOI: 10.1371/journal.pone.0173589
|View full text |Cite
|
Sign up to set email alerts
|

Distance in cancer gene expression from stem cells predicts patient survival

Abstract: The degree of histologic cellular differentiation of a cancer has been associated with prognosis but is subjectively assessed. We hypothesized that information about tumor differentiation of individual cancers could be derived objectively from cancer gene expression data, and would allow creation of a cancer phylogenetic framework that would correlate with clinical, histologic and molecular characteristics of the cancers, as well as predict prognosis. Here we utilized mRNA expression data from 4,413 patient sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Riester et al analysed mRNA expression data of histologically diverse cancer samples in comparison to gene expression in stem cell samples including human embryonic stem cells, human mesenchymal stem cells and CD34+ hematopoietic stem cells. The authors found that poor overall survival is correlated with gene expression signatures with the most similar expression to that of stem cells [ 160 ]. While it remains to be determined the extent of the overlap between these tissues specific metastatic program to the expression profile of CSCs, evidence have shown that metastatic cancer possess distinct stem-like gene expression signatures [ 161 163 ].…”
Section: Csc In Metastasismentioning
confidence: 99%
“…Riester et al analysed mRNA expression data of histologically diverse cancer samples in comparison to gene expression in stem cell samples including human embryonic stem cells, human mesenchymal stem cells and CD34+ hematopoietic stem cells. The authors found that poor overall survival is correlated with gene expression signatures with the most similar expression to that of stem cells [ 160 ]. While it remains to be determined the extent of the overlap between these tissues specific metastatic program to the expression profile of CSCs, evidence have shown that metastatic cancer possess distinct stem-like gene expression signatures [ 161 163 ].…”
Section: Csc In Metastasismentioning
confidence: 99%
“…Cancers, particularly those poorly differentiated cancers including the high-grade ER-negative breast cancers, glioblastomas, and bladder carcinomas, also express ES cell gene signatures ( Ben-Porath et al., 2008 ). Patients with cancers expressing a gene signature similar to that of stem cells exhibit poor overall survival ( Riester et al., 2017 ). Similarities between embryonic cells and cancer cells are also found in DNA methylation patterns and pioneer transcription factors and architectural proteins that regulate chromatin organization ( Larson and Yuan, 2012 ; Chiang et al., 2014 ; Dobersch et al., 2019 ).…”
mentioning
confidence: 99%
“…One important discovery reported here is related to the possibility of generating anti-cancer immunity not just toward "bulk" cancer cells but also toward primitive de-differentiated CSC-like MammoSphere cells. Indeed, in several cancers, gene expression programs have been identified to be similar to those of embryonic pluripotent stem cells, namely, a "stemness" profile which is associated to oncogenic de-differentiation in epithelial cancer progression by a gradual loss of a differentiated phenotype and acquisition of progenitor and stem cell-like features (7,8,57).…”
Section: Discussionmentioning
confidence: 99%